The Influence of Peer Group Method of Education on the Knowledge and Motivation of Pregnant Women in Anemia Prevention - Mariani Mariani; Dodik Hartono; Siti Nur Hasina (GLOBAL HEALTH SCIENCE GROUP, 2024)
Anemia is a nutritional problem that needs attention and is a public health problem in Indonesia. Anemia, which is generally called anemia, is a condition when the body lacks red blood cells or hemoglobin (Hb), where the Hb in the blood is at a level lower than the normal limit. The percentage of pregnant women who experience anemia is 48.9%, this means that around 5 out of 10 pregnant women in Indonesia suffer from anemia. If anemia in pregnant women is not treated, it will result in suboptimal growth and development of the fetus in the womb and has the potential to cause complications in pregnancy and childbirth, even causing maternal death. Objective: This research was conducted to determine